Atypical Presentation of PKDL due to Leishmania infantum in an HIV-Infected Patient with Relapsing Visceral Leishmaniasis - Celesia, Benedetto Maurizio (Hindawi Publishing Corporation, 2014)
We describe the case of an Italian patient with HIV infection who developed an atypical rash resembling post-kala-azar dermal leishmaniasis (PKDL) when receiving liposomal Amphotericin B (L-AMB) for secondary prophylaxis of visceral leishmaniasis (VL). At the time of PKDL appearance, the patient was virologically suppressed but had failed to restore an adequate CD4+ T-cell count. Histology of skin lesions revealed the presence of a granulomatous infiltrate, with lymphocytes, plasma cells, and macrophages, most of which contained Leishmania amastigotes. Restriction fragment length polymorphism-polymerase chain reaction was positive for Leishmania infantum. Paradoxically, cutaneous lesions markedly improved when a new relapse of VL occurred. The patient received meglumine antimoniate, with a rapid clinical response and complete disappearance of cutaneous rash. Unfortunately, the patient had several relapses of VL over the following years, though the interval between them has become wider after restarting maintenance therapy with L-AMB 4 mg/kg/day once a month. Even if rare, PKDL due to Leishmania infantum may occur in Western countries and represents a diagnostic and therapeutic challenge for physicians. The therapeutic management of both PKDL and VL in HIV infection is challenging, because relapses are frequent and evidence is often limited to small case series and case reports.